History education for transitional justice?: Challenges, limitations and possibilities for settler colonial Australia - Keynes, Mati (International journal of transitional justice, 2019)
In recent times, a conception of history education as facilitating truth, remembrance and critical thinking has been positioned as useful for transitional justice in divided societies, but this analysis has not been extended to settler states which are also characterized by prolonged division and state-administered violence. To explore this, the article draws on examples from Australia where scholars have been extending the framework of transitional justice in order to better address the structural nature of injustice in settler states. By investigating the uses of temporality and historicization in history education, it concludes that while disciplinary models might contribute to the popular theses of transitional justice by encouraging students to emulate the skills of the historian, these models would likely work to strengthen rather than challenge the legitimacy of the Australian settler state. Therefore, any attempts to align history education with reconciliation in Australia will require a rethinking of current disciplinary models.